Pengaruh Kualitas Pelayanan dan Kepuasan Konsumen terhadap Loyalitas Pelanggan di Toko Mebel Sinar Jaya, Losari, Brebes - Laeli Istifana; Syariefful Ikhwan; Muhammad Syaifulloh; Akbar Nuur PDW; Hendri Sucipto (Journal of Economics and Management (JECMA), 2019)
The purpose of this study is to determine and analyze the effect of service quality on customer loyalty, the effect of consumer satisfaction on customer loyalty, and the influence of service quality and customer satisfaction together on customer loyalty. Research Location at Sinar Jaya Shop, Losari, Brebes. Data This research uses a quantitative approach using a type of survey research. The collected data is analyzed by describing or describing through frequency and percentage tables. The research used includes explanatory research through associative research, which is research that aims to explain the relationship between two or more variables with the aim of obtaining valid data. The research data used is subject data in the form of opinions, attitudes, experiences or characteristics of a person or group of people who are the subject of the study. Data were obtained using questionnaires in the form of written lists of questions which were then shared with respondents to fill out, documents in the form of report cards from respondents, literature studies derived from several literature and other supporting readings. The results of this study are known to be the Adjusted R Square value of 0.533. The coefficient of determination of 0.533 expresses the magnitude of the contribution of independent variables (X1 and X2) of 53.30% in explaining the variability of dependent variables (Y). Based on the regression equation Y = 15.382 + 0.257 X1+ 0.194 X2 can be interpreted that every increase in one unit of service quality and customer satisfaction variables will increase the customer loyalty variable by 0.257 units of service quality, plus 0.194 units of customer satisfaction at a constant of 15,382.